Coming out narratives of older gay men living in New Zealand - Neville, S; Kushner, B; Adams, J (Wiley, 2015)
Aim: Explore the coming out narratives in a group of older gay men. Methods: A narrative gerontological approach was employed to explore the coming out narratives of older gay men. Semi-structured digitally recorded individual interviews were undertaken with 12 gay men aged between 65 and 81 years who lived in the community. Data were analysed using a narrative data analytic process. Results: Three collective narratives related to the coming out of older gay men were identified: 'early gay experiences', 'trying not to be gay' and 'acceptance'. Conclusion: Older gay men come from diverse socio-cultural backgrounds. However, they all grew up in an era where same-sex attraction was a criminal offence. The path to accepting being a gay man was individualised and stressful for these participants. Consequently health and social service providers need to support the ongoing development of resilience and provide a person-centred approach to care that promotes wellbeing.
Keywords: gay; gerontology; identity; older gay men; sexuality